Education mediating the associations between early life factors and frailty: a cross-sectional study of the UK Biobank. Issue 3 (2nd March 2023) - Maharani, Asri; Didikoglu, Altug; O'Neill, Terence W; Pendleton, Neil; Canal, Maria Mercè; Payton, Antony
Abstract : Objectives: Exposures in utero and during infancy may impact the development of diseases later in life. They may be linked with development of frailty, although the mechanism is unclear. This study aims to determine the associations between early life risk factors and development of frailty among middle-aged and older adults as well as potential pathways via education, for any observed association. Design: A cross-sectional study. Settings: This study used data from UK Biobank, a large population-based cohort. Participants: 502 489 individuals aged 37–73 years were included in the analysis. Primary and secondary outcome measures: Early life factors in this study included being breast fed as a baby, maternal smoking, birth weight, the presence of perinatal diseases, birth month and birth place (in or outside the UK). We developed a frailty index comprising 49 deficits. We used generalised structural equation modelling to examine the associations between early life factors and development of frailty and whether any observed association was mediated via educational attainment. Results: A history of breast feeding and normal birth weight were associated with a lower frailty index while maternal smoking, the occurrence of perinatal diseases and birth month with a longer day length were associated with a higher frailty index. Educational level mediated the relationship between these early life factors and frailty index. Conclusions: This study highlights that biological and social risk occurring at different stages of life are related to the variations in frailty index in later life and suggests opportunities for prevention across the life course.